A history of enterprise policy government, small business and entrepreneurship - Mallett, Oliver; Wapshott, Robert (New York, NY : Routledge, 2020)
Governments in developed and developing economies have increasingly turned to entrepreneurship and small businesses for economic growth, dynamism and economic and social inclusion. Policies seeking to encourage, support or otherwise influence these forms of economic activity are varied but virtually omnipresent, recommended by organisations such as the OECD and World Bank and implemented by governments of many political ideologies. With a range of activities across government labelled as enterprise policy, it is vital to unpick the different policies, initiatives and interventions and to understand their development in order to subject them to scrutiny and evaluate the actions taken in the name of enterprise. This book provides the first in-depth, historical analysis of enterprise policy in the United Kingdom. Successive UK governments have been particularly active, with the number of initiatives estimated recently at 3000 and expenditure reaching as high as 12bn, yet facing continuous criticisms for its use, value or relevance. This historical study of UK enterprise policy represents a case study of different forms of enterprise policy and how they have developed, or failed to develop, over time, contributing to understanding of government, small business and entrepreneurship. It will be of value to researchers, academics, policymakers, and students interested in the history of small business and entrepreneurship as well as standing as a history of a specific policy area and the ways in which policies involving many different areas of government develop over time.
OCLC-licensed vendor bibliographic record.
Keywords: Small business -- Government policy -- Great Britain -- History; Entrepreneurship -- Government policy -- Great Britain -- History; Industrial policy -- Great Britain -- History; BUSINESS & ECONOMICS / Entrepreneurship; BUSINESS & ECONOMICS / Small Business; BUSINESS & ECONOMICS / Government & Business